Porous polymer coatings as substrates for the formation of high-fidelity micropatterns by quill-like pens - Hirtz, Michael Manfred; Lyon, Marcus; Feng, Wenqian; Holmes, Andrea E.; Fuchs, Harald; Levkin, Pavel (Beilstein journal of nanotechnology, 2013)
Beilstein Journal of Nanotechnology
Gesehen am 05.01.2022